Biodiversity of Pneumocystis carinii hominis: typing with different DNA regions. - Latouche, S (1997)
The purpose of this study was to identify the most useful gene for the detection of biodiversity of Pneumocystis carinii hominis isolates and to compare samples from French and Italian subjects. We studied 20 bronchoalveolar lavage fluid specimens from 20 human immunodeficiency virus-infected patients (10 French and 10 Italian patients) with Pneumocystis carinii pneumonia by DNA sequencing of the thymidylate synthase (TS), 5S rRNA, large-subunit mitochondrial rRNA (mt LSU rRNA), and internal transcribed spacer (ITS1 and ITS2) genes. Thirteen of the 20 sequenced samples had the prototype TS gene sequence. Fourteen of the 20 samples showed the prototype sequence of the 5S rRNA gene, and 6 had variant sequences of the 5S rRNA gene. The mt LSU rRNA gene was sequenced for 18 of the 20 samples; all sequences were different from the prototype sequence and were classified into four groups. Thirteen of the 20 ITS1 and ITS2 sequences were analyzed, and all the sequences were found to be different from the prototype sequence and were classified into 10 groups. The internal transcribed spacer regions thus appear to be the most discriminatory region of DNA for analysis of the biodiversity of P. carinii hominis isolates.